Westwards and northwards dispersal of Triosteum himalayanum (Caprifoliaceae) from the Hengduan Mountains region based on chloroplast DNA phylogeography - Liu, Hai-rui; Gao, Qing-bo; Zhang, Fa-qi; Khan, Gulzar; Chen, Shi-long (PeerJ, 2018)
The varying topography and environment that resulted from paleoorogeny and climate fluctuations of the Himalaya–Hengduan Mountains (HHM) areas had a considerable impact on the evolution of biota during the Quaternary. To understand the phylogeographic pattern and historical dynamics of Triosteum himalayanum (Caprifoliaceae), we sequenced three chloroplast DNA fragments (rbcL-accD, rps15-ycf1, and trnH-psbA) from 238 individuals representing 20 populations. Nineteen haplotypes (H1–H19) were identified based on 23 single-site mutations and eight indels. Most haplotypes were restricted to a single population or neighboring populations. Analysis of molecular variance revealed that variations among populations were much higher than that within populations for the overall gene pool, as well as for the East Himalayan group (EH group) and the North Hengduan group (NHM group), but not for the Hengduan Mountains group (HM group). Ecoregions representing relatively high genetic diversity or high frequencies of private haplotypes were discovered, suggesting that this alpine herbaceous plant underwent enhanced allopatric divergence in isolated and fragmented locations during the Quaternary glaciations. The current phylogeographic structure of T. himalayanum might be due to heterogeneous habitats and Quaternary climatic oscillations. Based on the phylogeographic structure of T. himalayanum populations, the phylogenetic relationship of identified haplotypes and palaeodistributional reconstruction, we postulated both westwards and northwards expansion from the HM group for this species. The westwards dispersal corridor could be long, narrow mountain areas and/or the Yarlung Zangbo Valley, while the northwards movement path could be south–north oriented mountains and low-elevation valleys.
Keywords: Chloroplast DNA; Palaeodistributional reconstruction; Himalaya–Hengduan Mountains; Phylogeography; Range expansion